PENGARUH PELAYANAN DAN CITRA TOKO TERHADAP KEPUASAN UNTUK MENINGKATKAN LOYALITAS PELANGGAN PADA TOKO TIRTO DI KABUPATEN BREBES - Medi Tri Purwanto; Sri Ratih Handayani (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2022)
ABSTRACT This study aims to analyze the effect of service and store image on satisfaction to increase customer loyalty at Tirto Stores in Brebes Regency. Competition for product quality and price is so tight that it requires marketers to have quality products and prices that consumers can afford, and to be able to develop useful and innovative products in accordance with consumer expectations and market needs. branded in a place that is accessible to the public. Samples were taken by purposive sampling method of 117 people. Data was collected using the questionnaire method, namely by providing a list of questions or questionnaires directly to the respondents. The data analysis technique in this study uses the Structural Equation Model analysis. The results showed that service variables had no effect on customer loyalty but store image had a positive and significanteffect on loyalty, and customer satisfaction variables were able to mediatebetween service variables and store image on customer loyalty. Keywords: Service, Store Image, Satisfaction and Loyalty.